Rates of Internal Hiring of Ophthalmology Faculty from their Institution of Training at Top Academic Medical Centers: A Cross-Sectional Study - Rizk, Emanuelle M.; Wang, Jiangxia; Zhao, Xiyu; Tsou, Brittany; Metiku, Beruk E.; Cho, Katie; Samineni, Pranav; Sridhar, Jayanth; Woreta, Fasika A. (Journal of Academic Ophthalmology, 2023)
Background Throughout graduate and postgraduate education, trainees need to gauge the impact of training location on future institutions of practice.Objective We assessed rates of internal hiring of ophthalmology faculty at academic institutions from their same institution of training.Methods This was a cross-sectional study. We included 1,246 clinical ophthalmology faculty at the 13 top-ranked institutions listed in the 2021 U.S. News and World Report. Primary, emeritus, adjunct, and affiliate faculty were included. Publicly available information was collected from institutional websites and other online sources. Statistical analyses were conducted using t-tests or Mann–Whitney tests, chi-squared or Fisher's exact tests, and multivariate logistic regression. The main outcome measured was internal hires, defined as faculty who had completed residency and/or fellowship training at their current institution.Results In total, 47.3% of faculty were internal hires who completed residency or fellowship at the same institution. Among externally trained faculty, 27.7% completed residency and 56.0% completed fellowship at another top 13 programs. Internal hires were more frequently fellowship-trained, had a greater number of publications, and practiced in smaller departments (p < 0.001, p < 0.001, and p = 0.002, respectively). A greater proportion of internal hires held leadership positions (p = 0.012). Faculty practicing in the Midwest or West and with more years since residency graduation were less likely (odds ratio [OR], 0.29, 95% confidence interval [CI], 0.18–0.48; OR, 0.49, 95% CI, 0.31–0.78; OR, 0.98, 95% CI, 0.97–0.99, respectively) to be internal hires. Faculty with non-R01 National Institutes of Health funding were more likely to be internal hires (OR, 1.82, 95% CI: 1.12–2.96).Conclusions Training institution is key to determining the institution of practice. These results may be beneficial for trainees to consider when selecting a training program.
Keywords: Retention; Training location; Internal hiring; Residents and fellows; Fellowship; Ophthalmology faculty